ACCURACY OF URINE DIPSTICK TO PREDICT URINARY TRACT INFECTIONS IN AN EMERGENCY DEPARTMENT - Rehmani, Rifat (Journal of Ayub Medical College Abbottabad, 2004)
Background: Urine dipstick is a useful and commonly used test in the Emergency Department because of its rapidity and low cost; however its diagnostic accuracy is debatable. Our objective was to compare the urine dipstick and urinalysis for Urinary Tract Infection in a developing country, where there are significant cost considerations. Methods: This was an observational study of adults' patients presenting to Section of Emergency section (SEM) of the Aga Khan University Hospital, from March to May 1998. The patient's urine sample was tested immediately, using the Multistix 10SG. The sample was sent within one hour to the hospital laboratory for analysis, while the urinary specimen was sent for culture, where appropriate. The dipstick results were compared with the results of automated urinalysis in the laboratory, leukocyte counts on microscopy and urine culture. Sensitivity, Specificity, and predictive values were also calculated. Results: We evaluated 984 samples of urine during the study period. The sensitivity of nitrite test was 81% and that of leukocyte esterase 77% for positive cultures. However, the sensitivity for combined nitrite and leukocyte esterase test was 94%. Nitrite test was more specific (87%) than leukocyte esterase test (54%) or both tests taken together (50%). The predictive value of nitrite and leukocyte esterase together for a negative urine culture was 95%. Leukocyte esterase test sensitivity increased as the number of white blood cells on microscopy increased. Similarly the predictive value of leukocytes on microscopy for a positive culture increased as the number of leukocytes increased. Conclusion: Dipstick alone cannot accurately predict urinary tract infection in emergency department. Key Words: urine dipstick, urinary tract infection, and emergency department